TRADITIONS IN SOCIAL-CULTURAL RETROSPECTIVE - N. M. Mamedova (Научный вестник МГТУ ГА, 2016)
The article discusses the features of broadcast and traditions in the cultural space. Sociocultural retrospective reveals a wide variety of social programs transferring their experience, their organization in the tradition. The conclusion has been made about a complex tangle of demonstrative and imperative, nonverbal and verbal ways of creating and maintaining traditions.